O sintagma verbal em português: construções perifrásticas e não-perifrásticas - Paula, Danytiele Cristina Fernandes de [UNESP] (2014)
Based on a previous research, denominated Ordering of constituents in a verb phrase in portuguese varieties (FAPESP – Process 2010/19767-1), the proposal of this research is clarify the nature of periphrastic and non-periphrastic constructions of Portuguese language, by the application of auxiliarity tests and especially of the order of constituents in Portuguese verb phrase. For this, we consider the theoretical framework of Functional Discourse Grammar developed by Hengeveld and Mackenzie (2008), assuming the functional perspective to the ordination of the constituents and for the analysis of verbal constructions in Portuguese. The research universe are actual occurrences extracted of oral corpus organized by Linguistics Center of University of Lisbon in partnership with University of Toulouse-le-Mirail and the University of Provença-Aix-Marselha, which were selected samplings referred to the varieties that constitutes countries official language, in this case, brazilian, portuguese and africans. After the selection, the occurrences are analyzed according to the application of the auxiliarity tests, as presented in Castilho (2010): i) sharing the subject of the expression; ii) scope of negation; iii) semantic alteration of the auxiliary verb; (iv) insertion of expressions between the auxiliary verb and the main verb. The fourth test is related to the order of constituents, a factor that proved essential to the definition of periphrastic and non-periphrastic constructions in Portuguese, seeing that it shows the impossibility of treating the constructions with the verbs begin, continue, finish, pass, must, want, etc. as verb phrase. Thus, the results emphasize the features of the auxiliary verbs have, there to be and go (when indicates futurity) for the formation of the composite time; be and go for the indication of the progressive aspect (constructions formed with gerund); have to/for for constructions with deontic modality; showing ...